The Effectiveness of Using Smart Box Media on Children Raudhatul Athfal Amal Bakti Muslimin Marihat Bandar Simalungun North Sumatra - Wulandari, Dianty (Jurusan Pendidikan Islam Anak Usia Dini, 2024)
This study examines the pedagogical effectiveness of a multi-sensory learning tool, the